TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEPERAWATAN DI RUANG RAWAT INAP KELAS III RUMAH SAKIT PERTAMEDIKA UMMI ROSNATI (RSPUR) BANDA ACEH MARET-APRIL 2018 - Devi Fasrah; Aslinar Aslinar (Jurnal Sains Riset, 2021)
Hospitals as one of the health service subsystems provide two types of services for the community, namely health services and administrative services. The determinants of the level of customer or consumer satisfaction are also influenced by the characteristics of these consumers which are the characteristics of a person or the uniqueness of a person who distinguishes one with another. Ummi Rosnati Pertamedika Hospital (RSPUR) is a new hospital located in the city of Banda Aceh, RSPUR also provides facilities in the form of inpatient services with different classes such as VIP class, class I, class II and class III. A preliminary study conducted on 10 inpatients in Class III infant room consisting of 4 male patients and 7 female patients, showed 2 male patients and 4 female patients felt that nursing care in RSPUR was good because nurses always pay attention to patients, while 2 other male patients and 3 other female patients stated that nursing service is still lacking. This study aims to analyze the quality of patient care services inpatient class III RSPUR with the level of satisfaction with nursing services provided by medical personnel. This research is useful for It is hoped that the results of this study can contribute information for the development of science of State Administration, especially the study of the implementation of public services (Hospital). This research uses crossectional study type of study conducted at RSPUR Banda Aceh City in April of 2018. This research was designed with non experimental quantitative technique with 66 samples. The results of research in though by using univariate data analysis by calculating the frequency of distribution in the form of percentage of distribution tables. The results showed that patients were very satisfied with the nursing service provided by third class medical personnel RSPUR Kota Banda Aceh with the percentage of patient satisfaction of 92.4%. The conclusion of this study patients feel very satisfied on the performance and servants nursing class III RSPUR given to patients.Keywords: Level of Satisfaction, Aspect of Nursing Service, Patient Class III RSPUR